Hemotropic mycoplasmas in naturally infected cats in northeastern Brazil - Munhoz, Alexandre Dias; Simões, Izabela Garcia Pinto Coelho; Calazans, Ana Paula Fernandes; Macedo, Ludimila Santos; Cruz, Rebeca Dálety Santos; Lacerda, Luciana Carvalho; Said, Roueda Abou; André, Marcos Rogério [UNESP] (FapUNIFESP (SciELO), 2018)
This study aimed to determine the prevalence, factors associated, laboratory findings (with and without coinfection by retroviruses) among naturally infected cats by hemoplasmas in northeastern Brazil. For convenience, 200 domesticated and healthy cats were selected. Blood samples were taken to perform complete blood counts, serum biochemical, immunochromatography tests and nPCR for FIV and FeLV, and PCR for hemoplasma recognition. An interview was conducted to determine the factors associated with hemoplasmas. A total of 71/200 (35.5%) cats were positive for at least one hemoplasma species. Isolated infections were observed in 12,5% for ‘Candidatus Mycoplasma haemominutum’, 12% for Mycoplasma haemofelis and 3% for ‘Candidatus Mycoplasma turicensis’. Regarding copositivity, 2% of the animals were positive for M. haemofelis and ‘Candidatus Mycoplasma haemominutum’, 1.5% for M. haemofelis and ‘Candidatus Mycoplasma turicensis’, and 4.5% for ‘Candidatus Mycoplasma haemominutum’ and ‘Candidatus Mycoplasma turicensis’. No clinical and laboratory changes were observed in the animals that were concomitantly positive for retroviruses and hemoplasmas. Periurban region cats were more likely to be infected by M. haemofelis, while contact with other cats and infection by ‘Candidatus Mycoplasma turicensis’ were associated with ‘Candidatus Mycoplasma haemominutum’. This study indicates that infection by hemoplasmas is a common find in cats from northeastern Brazil.
Micoplasmas hemotróficos em gatos naturalmente infectados no nordeste do Brasil
Keywords: Hemoplasmas; Mycoplasma haemofelis; Retrovirus; ‘candidatus Mycoplasma Haemomominutum’; ‘candidatus Mycoplasma turicensis’